2020
DOI: 10.14569/ijacsa.2020.0110972
|View full text |Cite
|
Sign up to set email alerts
|

Hate Speech Detection in Twitter using Transformer Methods

Abstract: Social media networks such as Twitter are increasingly utilized to propagate hate speech while facilitating mass communication. Recent studies have highlighted a strong correlation between hate speech propagation and hate crimes such as xenophobic attacks. Due to the size of social media and the consequences of hate speech in society, it is essential to develop automated methods for hate speech detection in different social media platforms. Several studies have investigated the application of different machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…The introduction of linguistic features might be a promising path [45,59]. A further improvement to this task could be to incorporate textual and image data together in the detection models [12,37,74]. For possible work corresponding to the hate speech task, the examination of platforms other than Twitter that fertilizes hate speech could be explored, as suggested by [86].…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of linguistic features might be a promising path [45,59]. A further improvement to this task could be to incorporate textual and image data together in the detection models [12,37,74]. For possible work corresponding to the hate speech task, the examination of platforms other than Twitter that fertilizes hate speech could be explored, as suggested by [86].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Nevertheless, they suffered from ineffective sequence acodingly representation. As such, the transformer-based method was provided by [74]. In [86], researchers noted that hate speech can be directed at a single person or a group of people (generalized).…”
Section: Other Challengesmentioning
confidence: 99%
“…Though earlier methods have been limited in their usefulness as they often can only handle obvious patterns, encouragingly, the present transformer-based deep learning models have reached a much higher accuracy (Acc.) of more than 90% in detecting textual hateful messages due to its powerful capacity in the semantic comprehension [ 17 ]. The commercial application of deep learning models effectively reduces the spreading of textual hateful messages.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, content moderators are known to suffer post-traumatic stress disorder (PTSD)-like syndromes after repetitively reviewing violent and exploitative content [9]. As a result, generations of automatic hateful message detection methods have been developed since 2009, from the initial block-word-list approach to the current deep learning-based technology [10][11][12][13][14][15][16][17]. Though earlier methods have been limited in their usefulness as they often can only handle obvious patterns, encouragingly, the present transformer-based deep learning models have reached a much higher accuracy (Acc.)…”
Section: Introductionmentioning
confidence: 99%
“…The authors, focusing exclusively on the Transformer-based RoBERTa, demonstrated that large pretrained Transformer LMs are highly potent in classification tasks even when the dataset size is very small as compared to most other deep learning applications. Mutanga et al (2020) also evaluated an ensemble of Transformer models, focusing mainly on the DistilBERT model, which is a scaled-down version of the original BERT with increased speed while maintaining considerable consistency in performance.…”
Section: Introductionmentioning
confidence: 99%